Phytochemical constituents and allelopathic potential of Parthenium hysterophorus L. in comparison to commercial herbicides to control weeds - Motmainna, Mst.; Juraimi, Abdul Shukor; Uddin, Md. Kamal; Asib, Norhayu; Islam, A. K. M. Mominul; Ahmad Hamdani, Muhammad Saiful; Hasan, Md Mahmudul (MDPI AG, 2021)
The allelopathic effect of various concentrations (0, 6.25, 12.5, 50 and 100 g L−1) of Parthenium hysterophorus methanol extract on Cyperus iria was investigated under laboratory and glasshouse conditions. No seed germination was recorded in the laboratory when P. hysterophorus extract was applied at 50 g L−1. In the glasshouse, C. iria was mostly injured by P. hysterophorus extract at 100 g L−1. The phytochemical constituents of the methanol extract of P. hysterophorus were analyzed by LC-ESI-QTOF-MS=MS. The results indicated the presence of phenolic compounds, terpenoids, alkaloids, amino acids, fatty acids, piperazines, benzofuran, indole, amines, azoles, sulfonic acid and other unknown compounds in P. hysterophorus methanol extract. A comparative study was also conducted between P. hysterophorus extract (20, 40 and 80 g L−1) with a synthetic herbicide (glyphosate and glufosinate ammonium at 2 L ha−1) as a positive control and no treatment (negative control) on Ageratum conyzoides, Oryza sativa and C. iria. The growth and biomass of test weeds were remarkably inhibited by P. hysterophorus extract. Nevertheless, no significant difference was obtained when P. hysterophorus extract (80 g L−1) and synthetic herbicides (glyphosate and glufosinate ammonium) were applied on A. conyzoides.